Software Test Attacks to Break Mobile and Embedded Devices - Hagar, Jon Duncan (Chapman & Hall/CRC innovations in software engineering and software development, 2013)
This book presents an attack basis for testing mobile and embedded systems in "smart" devices. It explains patterns and techniques ranging from simple mind mapping to sophisticated test labs. For traditional testers moving into the mobile and embedded area, the book bridges the gap between IT and mobile/embedded system testing. It illustrates how to apply both traditional and new approaches. For those working with mobile/embedded systems without an extensive background in testing, the book brings together testing ideas, techniques, and solutions that are immediately applicable to testing smart and mobile devices.